The change of power and politics in the information epoch - Авксентьєва, Т. Г.; Тихонова, Л. А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The specificity of social and political processes in the information epoch is observed. The main political characteristics of the digital division between societies are analyzed. In particular, author concerns societies that have the material and cultural conditions for their existence in the world of information and those who do not have them. It is alleged that the power in the information epoch belongs to those who are able to create new cultural codes.